Design and development of aircraft cargo fire early detection simulation system using arduino nano microcontroller - Chitraningrum, Nidya; Siswanti, Sri Dessy; Herdiana, Dina; Prasetiawan, Anton; Banowati, Lies; Muchtar, Kahlil; Sakti, Indra (Jurnal Teknika, 2024)
Fire in the aircraft cargo can cause dangerous damage to aircraft systems during flight. To prevent aircraft cargo fires, the fire early detection system must be built. In this work, we design and develop the fire early detection simulation system for aircraft cargo using Arduino nano microcontroller. The aircraft cargo is prone to fire due to the load of any type of goods such as dangerous goods, flammable stuff, or liquids, etc. This paper simulates the fire that occurs in artificial aircraft cargo and designs the detection and extinguisher prototypes using three kind sensors: flame, smoke, and temperature sensors combined with SMS gateway for user notification.  We used SIM800L GSM module as communication tools to send and achieve data through short messages service (SMS) between security system and cellphones. Three sensors including flame, smoke, and temperature sensors were used as the warning indication to the hardware. When the sensors detect the fire and smoke, the red LED, buzzer, and vacuum pump will be on active mode, and SMS notification will be delivered immediately to the user’s cell phone. As the fire has been extinguished by the vacuum pump, the red LED, buzzer, and vacuum pump return to standby mode and the fire warning alarm system will turn off. This research is successfully developing the fire early detection simulation systems that can be applied in real aircraft cargo.